ESTRATEGIAS COMUNICACIONALES EN LA EDUCACIÓN INCLUSIVA DE LOS ESTUDIANTES DE LA ESCUELA DE EDUCACIÓN ESPECIAL DE LA DIRECCIÓN DE GESTIÓN DE DESARROLLO SOCIAL DE QUEVEDO- EX-PAMUNIQ, AÑO 2022. - Coello Palma, Joyce Mariana (2022)
The objective of this research was to analyze the communication strategies focused on inclusive education for students of the school of special education of the management direction of social development of Quevedo- EX-PAMUNIQ, year 2022, for the development and support of this research began with a bibliographic study based on the two variables of study, The methodology used was framed in several techniques of data collection, such as a field research to collect updated and true information of the study area, it is of a mixed nature since interviews were conducted with the principal of the institution and teachers and surveys of parents of the institution; At the same time, a survey was conducted with the parents to further detail the characteristics of the needs of the population. As a result of this, those involved expressed their agreement to implement in their Annual Curricular Plan a chapter dedicated to inclusive communication strategies, so it is concluded that this research will help to improve the educational quality of the institution.